Debating Societies, the Art of Rhetoric and the British House of Commons: Parliamentary Culture of Debate before and after the 1832 Reform Act (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
British debating societies are here looked at a parliamentary perspective. The main emphasis is on the rhetorical practise of parliamentary debate, which, it is argued, constitutes the main framework of the British culture of debate. This will be approached from the perspective of how the parliamentary practises were reflected in the activities of various debating societies before and after the 1832 Reform Act. I will highlight that the rhetorical traditions of the British House of Commons were not formed in a vacuum, but, rather, shaped and adapted to constitutional changes. After the 1832 reform the practises in debating societies imitated the procedure and rules of the House of Commons more closely than before. The latter part of the essay concentrates on William Gladstone’s interpretation of parliamentary debate, himself having actively contributed to various student debating societies. Gladstone’s approach on debate in Parliament illustrates a more general shift in rhetorical practise away from the category of public speaking and towards a more proceduralised way of understanding parliamentary eloquence.